A hierarchical cluster analysis of the psycological impact of the COVID-19 pandemic on Italian severe asthma patients - Guarnieri, G; Chiurato, L; Baiardini, I; Caminati, M; Senna, G; Scarpa, B; Vianello, A (The Journal of asthma, 2023)
In the context of COVID-19 pandemic, a consistent medical concern raised among severe asthma patients, though the studies excluded an increased risk of severe disease as well as an increased susceptibility.The aim of the study was to apply the Psychological General Well-Being Index (PGWBI) questionnaire to severe asthmatics during the COVID-19 pandemic and to evaluate the data with a hierarchical cluster analysis. 114 severe asthmatics were asked to respond anonymously to the PGWBI questionnaire. The patients underwent a lung functional test, fractional exhaled nitric oxide (FeNO) measurement, Asthma Control Test (ACT), and Asthma Control Questionnaire (ACQ6). A hierarchical cluster analysis was performed using an agglomerative approach and complete linkage to evaluate the results. The study population predominantly included female (60%), middle-aged patients, with normal lung function parameters, mild signs of airway, and satisfactory asthma control. The PGWBI score (82.46 ± 16.53) of the study population showed a good state of psychological well-being and was similar to that of a representative sample of healthy adult Italian subjects. Thus, Hierarchical cluster analysis identified 3 groups of patients: Cluster 1 (32%), Cluster 2 (64%), and Cluster 3 (4%). Whilst the Cluster 2 patients' PGWBI score fell within the normal range, the Cluster 1 patients had a significantly lower total score (68.57 ± 7.2; < 0.05), suggesting moderate distress. The Cluster 3 patients presented a total score markedly low. Although the majority of the severe asthma patients studied demonstrated good mental well-being during the COVID-19 pandemic, some did indeed show moderate to severe psychological distress.